Women’s thirty-year contribution to cheetah conservation: An insight into volunteer-based conservation program supported by female scientists - Marker, Laurie; Pfeiffer, Lauren; Maketo, Tracy; Pöntinen, Annetjie (Frontiers in Conservation Science, 2022)
Women make up a small percentage of the scientific community, including conservation. Today, conservation efforts are vital for the survival of many species, however there is a gender bias within the conservation field. Encouraging more women into conservation could be a key to increasing efficiency and success in conservation goals of organizations and governments. Here we investigate the long running Earthwatch, working guest and intern volunteer programs of the Cheetah Conservation Fund (CCF) to understand women’s involvement with volunteer based conservation, and questionnaire data to understand women’s contribution to conservation after volunteering and what challenges women face in conservation. Our results showed there was significantly more female volunteers than male volunteers (p-value <0.000) and on average, females contributed to 73.7% of the volunteer population annually. Volunteer’s age at time of volunteering varied between the three volunteer programs. Women’s motivations for volunteering and challenges that women face in conservation was dependent on the volunteers’ age. CCF’s holistic approach to conservation, volunteers’ love for cheetahs and ability to gain practical skills were the leading motivations why women volunteered with CCF. Many (87%) of the female interns said volunteering was a means of helping them gain employment. Women’s credibility, family responsibility and personal safety were the main challenges that women face working in conservation today. Addressing gender disparities in every stage of career progression will lead to overall improved conservation outcomes.